2018
DOI: 10.3892/br.2018.1118
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 is important for regulation of core body temperature during long-term cold exposure in mice

Abstract: Interleukin-6 (IL6) is a cytokine important for inducing the fever response during infection and has been reported to uphold core body temperature during acute cold exposure. Recently it has also been indicated that IL6 in serum increases in cold-exposed mice. The aim of the present study was to investigate if IL6 is important for core body temperature regulation following a long-term cold exposure in mice. Experiments were performed with global IL6 deficient (-/-) mice, mice with conditional IL6 receptor α (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…Thus, IL6 deficient mice exhibited decreased NE levels after stress challenge but similar increases in EE to those found in control mice after peripheral NE treatment. In line with these findings, lower rectal or core body temperatures than controls have been reported in other mouse models with tissue specific IL6 [ 195 ] or IL6RA deletion [ 196 ] (muscle and CNS) when maintained at warm or cold environments.…”
Section: Cytokines: Immune Actors In Bat Activation and Browning Osupporting
confidence: 81%
“…Thus, IL6 deficient mice exhibited decreased NE levels after stress challenge but similar increases in EE to those found in control mice after peripheral NE treatment. In line with these findings, lower rectal or core body temperatures than controls have been reported in other mouse models with tissue specific IL6 [ 195 ] or IL6RA deletion [ 196 ] (muscle and CNS) when maintained at warm or cold environments.…”
Section: Cytokines: Immune Actors In Bat Activation and Browning Osupporting
confidence: 81%
“…IL-6 -/mice develop obesity during aging mostly because of the missing effects of the cytokine on the central nervous system [43]. Recently, it was shown that these mice have reduced core body temperature and energy expenditure during long-term cold exposure [44]. Mice overexpressing IL-6 and the soluble IL-6R are significantly smaller and have a decreased body weight including markedly reduced body fat in all regions as compared to wild type mice [45].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 6 (IL-6) is secreted by brown adipocytes upon β-adrenergic activation (62). Chronic elevation of IL-6 in the CNS leads to increased UCP1 in BAT, but not in denervated BAT tissue which suggest a central role in IL-6-dependent promotion of thermogenesis (174). Signaling by IL-6 promotes M2 macrophage polarization in BAT (175).…”
Section: Brown Adipocytes Secrete Pro/anti-inflammatory Mediatorsmentioning
confidence: 96%